2015
DOI: 10.18632/oncotarget.5371
|View full text |Cite
|
Sign up to set email alerts
|

Detection of recurrent cytogenetic aberrations in multiple myeloma: A comparison between MLPA and iFISH

Abstract: Multiple myeloma (MM) is a genetically heterogeneous disease with diverse clinical characteristics and outcomes. Recently, multiplex ligation-dependent probe amplification (MLPA) has emerged as an effective and robust method for the detection of cytogenetic aberrations in MM patients. In the present study, MLPA analysis was applied to analyze cytogenetics of CD138 tumor cells of 59 MM samples, and its result was compared, retrospectively, with the interphase fluorescence in situ hybridization (iFISH) data. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Our study is the first large-scale study investigating the miR-424-3p and CTLA-4 pathway in human prostatectomy specimens (no = 535), we also abled to investigate the correlation to PD1, PD-L1 and subset of T cells. Herein, we found that a low expression of miR-424-3p was significantly correlated to aggressive PC phenotype, worse clinical outcome and reduced time for clinical failure, which is in line with previous in vitro and in vivo studies 36,38,4246 . We also identified a correlation between miR-424-3p, CTLA-4 and PD-L1, which is in accordance with one previous report 12 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study is the first large-scale study investigating the miR-424-3p and CTLA-4 pathway in human prostatectomy specimens (no = 535), we also abled to investigate the correlation to PD1, PD-L1 and subset of T cells. Herein, we found that a low expression of miR-424-3p was significantly correlated to aggressive PC phenotype, worse clinical outcome and reduced time for clinical failure, which is in line with previous in vitro and in vivo studies 36,38,4246 . We also identified a correlation between miR-424-3p, CTLA-4 and PD-L1, which is in accordance with one previous report 12 .…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Zhang et al . reported a functional role of miR-424/Akt3/E2F3 axis in hepatocellular carcinoma development, suggesting that miR-424 could be a potential indicator of prognosis 36 . In PC there is only a limited number of studies and they all has limitation mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…De novo resistance is present before the drug exposure and then selected during the drug treatment [ 3 ]. Recent studies have demonstrated, by inter-phase fluorescence in situ hybridization (iFISH) [ 5 ] and flow cytometry [ 6 ], the heterogeneity of MM cells at genetic (chromosome number, genetic translocations and mutations), clonal and cell differentiation levels. In particular, flow cytometry analysis reveals the presence of multiple cell clones in patients at diagnosis that are selected by in vivo therapeutic pressure and induce a distinct phenotypic MM cell subclone with different clonogenic and cytogenetic profiles in minimal residual disease [ 6 ].…”
Section: Drug Resistancementioning
confidence: 99%
“…MM is a B cell differentiated tumor characterized by clonal proliferation of tumor cells [13]. MM is a heterogeneous disease with different clinical characteristics [4]. By recognizing genetic mechanism and mutation, a normal plasma cell transited into the following disease stages: monoclonal gammopathy of undetermined significance, smouldering myeloma, myeloma and plasma cell leukaemia [5].…”
Section: Introductionmentioning
confidence: 99%